Effects of sample handling on the detection of porcine reproductive and respiratory syndrome virus in oral fluids by reverse-transcription real-time PCR. (November 2018) - Weiser, Ashley C.; Poonsuk, Korakrit; Bade, Sarah A.; Gauger, Phillip C.; Rotolo, Marisa; Harmon, Karen; Gonzalez, Wendy M.; Wang, Chong; Main, Rodger; Zimmerman, Jeffrey J.
We evaluated effects of handling procedures on detection of porcine reproductive and respiratory syndrome virus (PRRSV) in oral fluids (OFs) by reverse-transcription real-time PCR (RT-rtPCR). The experiments were conducted using a composite sample of PRRSV-positive OF collected from 5-wk-old pigs vaccinated 15 d earlier with a modified-live PRRSV vaccine. Five pre-extraction sample-handling steps and all combinations thereof were evaluated: 1) thaw temperature (4°C or 25°C); 2) sample diluent (1:1 dilution with nuclease-free water or guanidinium thiocyanate–phenol); 3a) sonication of the sample (yes or no); 3b) temperature (4°C or 25°C) at which step 3a was conducted; and 4) temperature at which the sample was maintained after step 3b and until RNA extraction was initiated (4°C or 25°C). All combinations of the 5 sample-handling steps (i.e., 32 unique treatments) were tested in a completely randomized factorial design with 4 replicates and 1 negative control for each treatment. The entire experiment was repeated on 5 separate days to produce a total of 800 PRRSV RT-rtPCR results. Binary (positive or negative) data were analyzed by logistic regression and results (Ct) were analyzed using a generalized linear model. Overall, 1 false-positive result was observed among 160 negative controls (99.4% specificity), and 85 false-negative results were observed among the 640 known-positive samples (86.7% sensitivity). The most significant factor affecting test outcome was thaw temperature (4°C or 25°C); samples thawed at 4°C had higher positivity rate (94% vs. 80%, p < 0.0001) and lower Ct (36.2 vs. 37.5, p < 0.0001).